Internalization of Pancasila Values in Catholic Schools: Efforts to Strengthen National Commitment - Buaq, Desiana; Lorensius, Lorensius (PT Literasi Nusantara Publisher, 2022)
Extremism and radicalism have become severe problems spreading rapidly worldwide, even reaching educational institutions in Indonesia. In response, Catholic schools have developed learning that contains Pancasila values. This article aims to describe the importance ​​of Pancasila in Catholic schools, focusing on how students' learning experiences in schools with elements of Pancasila values ​​form character within themselves. To find this, this study uses a qualitative approach. Observation, interview, and documentation methods were used to collect data from three informants: the vice principal, teachers, and students. The collected data were analyzed descriptively. This study found that students in Catholic schools get learning experiences that include Pancasila values to foster character in students to be tolerant, harmonious, non-violent, willing to accept differences, and respect diversity. Pancasila values ​​are applied in direct learning in class and flag ceremony activities every Monday, ceremonies commemorating Heroes' Day, Independence Day, and Teacher's Day, and implementing a welcoming and friendly school culture. This model can become a 'best practice' for schools to direct the education system towards peace-loving, inclusive and humanistic values and ensure that the matters ​​contained in Pancasila effectively strengthen students' national commitment.